2021
DOI: 10.1002/dev.22111
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent stress during, but not after, pubertal onset impairs indices of prepulse inhibition in adult rats

Abstract: Exposure to stress during adolescence is a risk factor for developing several psychiatric disorders, many of which involve prefrontal cortex (PFC) dysfunction. The human PFC and analogous rodent medial prefrontal cortex (mPFC) continue to mature functionally and anatomically during adolescence, and some of these maturational events coincide with pubertal onset. As developing brain regions are more susceptible to the negative effects of stress, this may make puberty especially vulnerable. To test this, we expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 129 publications
(160 reference statements)
0
7
0
Order By: Relevance
“…Another example of differential timing comes from work on pre-pulse inhibition (PPI), a task that relies on the mPFC [41,42]. PPI is deficient in females that experienced daily restraint stress during early, but not late, adolescence [22]. Interestingly, PPI was also deficient in males when the stress was applied peri-pubertally which coincides with late adolescence in the present study, and males were not affected even later, but post-pubertal, in adolescence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another example of differential timing comes from work on pre-pulse inhibition (PPI), a task that relies on the mPFC [41,42]. PPI is deficient in females that experienced daily restraint stress during early, but not late, adolescence [22]. Interestingly, PPI was also deficient in males when the stress was applied peri-pubertally which coincides with late adolescence in the present study, and males were not affected even later, but post-pubertal, in adolescence.…”
Section: Discussionmentioning
confidence: 99%
“…This all suggests that adolescence may be a time of increased negative consequences of stimulant use, particularly for females, which coincides with the development of PV neurons and PNNs in the mPFC. Timing of exposure within adolescence may also be important since many structural changes occur around female puberty [10, 21], and both sexes are behaviorally more sensitive to stress peri-pubertally in adolescence [22].…”
Section: Introductionmentioning
confidence: 99%
“…It has been further suggested that the PFC mediates the attentional enhancement of PPI of the acoustic startle reflex ( Meng et al, 2020 ). Additionally, prefrontal dysfunction caused by isolation stress during adolescence resulted in PPI deficits ( Drzewiecki et al, 2021 ; Du et al, 2021 ). What other brain areas are involved in and how the brain network subserving attention is involved in this process need further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Both peri-pubertal stressed males and females have lower PPI scores (less sensorimotor gating) than control and post-pubertal stressed rats. *p < .05, ***p < .001 (Drzewiecki, Willing et al, 2021).…”
Section: F I G U R E 1mentioning
confidence: 96%
“…This occurred in parallel in both sexes in spite of a main effect of sex such that females had lower PPI scores than males. It is also notable that the age of the post-pubertal females overlapped the age of the peripubertal males (Drzewiecki, Willing et al, 2021).…”
Section: Timing Within Adolescence Mattersmentioning
confidence: 97%